Industry 4.0 in New Zealand dairy industry. (26th June 2019) - Aziz, Fariz; Samsudin, Shaqir; Nambiar, Neeraj; Aziz, Uthman; Li, Eric; Zhong, Ray Y.
New Zealand may be has the largest dairy industries in the world due to natural resources suitable for cows. It is facing new opportunities because a new generation of industry termed as Industry 4.0 is coming. Facing the new technologies, how traditional dairy industry in New Zealand could seize the golden opportunities in the context of Industry 4.0 to upgrade and transform? This paper analyses the current status of New Zealand dairy industry and gives some investigation results. Some significant insights and lessons from this study could be used for guiding dairy industry which is contemplating the implementation of Industry 4.0 enabled solutions.